Adolescent close friendships, self-perceived social acceptance, and peer-rated likeability as predictors of wellbeing in young adulthood - Shah, Emily N.; Szwedo, David E.; Allen, Joseph P. (Frontiers in Developmental Psychology, 2024)
Links between interpersonal relationships and physical and psychological functioning have been well established in the literature. During adolescence, success or distress in peer relationships may have distinct effects on different aspects of well-being. The present study aims to examine the ways in which different adolescent peer relationship contexts (i.e., close friendship quality, social acceptance, and likability from peers) can predict outcomes relevant to adult well-being (i.e., social anxiety, depression, aggression, social integration, romantic insecurity, job satisfaction, and physical health). Further, the study considers how different developmental stages of adolescence may impact links between peer relationships and well-being outcomes. Peer relationship contexts were assessed in early (ages 13-14) and late (ages 17-18) adolescence.Markers of well-being were measured in young adulthood (ages 28-30). A path analysis was used to examine whether the developmental timing of adolescent peer relationship contexts could predict well-being in young adulthood. Results suggest that, across adolescence, broader perceived social acceptance may be a more robust predictor of adult well-being compared to close friendship quality and peer likability. When examined at early and late adolescence separately, early adolescent social acceptance and late adolescent close friendship quality best predicted outcomes of adult well-being. Implications and considerations for future research are discussed.